2019
DOI: 10.1080/07420528.2019.1703732
|View full text |Cite
|
Sign up to set email alerts
|

Time-of-day variation on performance measures in repeated-sprint tests: a systematic review

Abstract: The lack of standardization of methods and procedures have hindered agreement in the literature related to time-of-day effects on repeated sprint performance and needs clarification. Therefore, the aim of the present study was to investigate and systematically review the evidence relating to time-of-day based on performance measures in repeated-sprints. The entire content of PubMed (MEDLINE), Scopus, SPORTDiscus® (via EBSCOhost) and Web of Science was searched. Only experimental research studies conducted in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Following the familiarisation process, all participants then completed two identical experimental sessions which took place 10 days apart to minimise any learning effect and to exclude any muscle soreness. Both sessions were conducted at the same time-of-day to reduce potential influence of circadian rhythmicity [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Following the familiarisation process, all participants then completed two identical experimental sessions which took place 10 days apart to minimise any learning effect and to exclude any muscle soreness. Both sessions were conducted at the same time-of-day to reduce potential influence of circadian rhythmicity [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Following the incremental cycling test, each participant completed a cycling exercise at constant or alternated intensities, in the morning 08:00 (AM) or in the late afternoon 18:00 (PM). The sessions were randomized and counterbalanced in order of administration to minimize any learning effects [11,25]. The intervals between testing sessions for recovery were at least equal to 48 hours.…”
Section: Experimental Designmentioning
confidence: 99%
“…Many chronobiological field studies have demonstrated diurnal variation in cycling performance [1,[20][21][22][23][24][25][26]. Poorer performances are commonly observed in the AM, while best performances are attained in the PM [5,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations